ANALISIS KECAP SEREPAN DINA KARANGAN BERITA SISWA PIKEUN BAHAN PANGAJARAN NULIS DI KELAS X SMAN 15 GARUT - Nur Aisah, - (2012)
This thesis is titled "Ketchup analysis Serepan dina News Student Essay writing Pangajaran pikeun Materials in Class X SMAN 15 Main Page". The method used in this study is a description of the method using the techniques of essay writing test news given to class X SMAN 15 Garut. This research aims to describe and analyze the uptake of words contained in the news article. In this case, students may not know all the words serepan into the language. This study succeeded in collecting 74 words uptake. The data is classified into the role in several groups, among them: 1) said the uptake in the form of the original absorbance said there were 42 words (56.75%) of the origin of the word shape analysis can be classified again according to the pattern of syllables that includes two syllables there are 27 words (64.28%), there are 11 three-syllable words (26.19%), there are four four-syllable words (9.52%) and five syllables there is one (2.38%). Words form the word serepan berimbuhan uptake (rundayan) there are 32 words (43.24%) which could dklasifikasikan again by the end of that covering affixes affixes-ion there are 14 words (43.75%), affixes-er there are three (9.37% ) words, affixes-s there are three (9.37%) said, there is uo-ive 4 (12.05%) said, there are 3 uo-ic word (9.37%), there are four affixes-al (12, 05%) and one (3.12%) which affixes-ing, 2) analysis according to type 46 words include words (62.16%) nouns, 11 words (14.86%) verbs, and there are 17 words (23.28%) adjective; 3) analysis of the meaning or meanings of each word there are 74 words contained in it and the meaning of the lexical meanings Based having a different meaning to each other, and 4) analysis of materials according to the word uptake in news article written by the students, said the uptake in the uptake word essay and implementation in the form of exercise to make sentences. The results of this study can be utilized for all parties, especially to enrich the vocabulary of the language.